Two cases of cardiac haemangioma on cardiac magnetic resonance in adolescents - Sitarska, Zuzanna; Barczuk-Falęcka, Marzena; A. Małek, Łukasz; Werner, Bożena; Kamińska, Halszka; Brzewski, Michał (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Cardiac haemangioma in children is a very rare benign tumour, which can lead to life-threating complications such as stroke or sudden death. There is no obvious correlation with age, sex, or family history. Symptoms depend on the location of the mass and can be non-specific. The tumour may be detected by echocardiography, but cardiac magnetic resonance (CMR) imaging allows evaluation of its size and accurate location as well the tissue characteristics. The aim of our report is to present cases of adolescent patients with cardiac haemangiomas. We present their symptoms, the diagnostic process, and possible treatment of this disease. The CMR and computed tomography (CT) images were included to present the characteristic features of cardiac haemangioma and its possible complications.